Toxicological Effects of Thifluzamide on the Embryonic Development & Hatchability of Channa Punctatus Eggs - Singh, Abhimanyu; Pandey, Dr. Rittika (American Journal of Bioscience and Clinical Integrity, 2025)
The agrichemical fungicide thifluzamide inhibits succinate dehydrogenase and addresses several crop fungal infections. Though it helps agriculture, concerns are emerging about its effects on aquatic life. Thifluzamide's toxicological effects on Channa punctatus embryonic evolution and hatchability are examined here. The spotted snakehead, a freshwater fish important ecologically and economically in many locations, is studied. Assessing environmental dangers and creating rules requires understanding how agricultural pesticides affect early organism growth. This study examines thifluzamide's effects on Channa punctatus embryos to assess aquatic environment risks. Fertilised Channa punctatus eggs were exposed to ambient and higher thifluzamide concentrations to imitate contamination. Mortality, developmental anomalies, and hatching success were carefully documented. Concentration increased death rates and head, spine, and tail abnormalities. Indeed, hatching was delayed. High thifluzamide levels slowed hatching, suggesting it may affect embryonic evolution. Channa punctatus embryos are vulnerable to thifluzamide and its effects on freshwater. Fish populations, biodiversity, and aquatic ecosystems are affected by toxicology. Agriculture's thifluzamide hazards endanger natural equilibrium. Regulations and others may use the data to limit and monitor thifluzamide application more carefully. Vigilance is essential to reduce thifluzamide's harmful effects on non-target aquatic species. It emphasises the need for agricultural pesticide environmental risk assessments to protect freshwater ecosystems and their populations. The destiny of local waterways is uncertain without immediate intervention.